Choledochoduodenostomy in the Management of Choledocholithiasis - Jan, Atta Ullah; Arif, Muhammad (Journal of Postgraduate Medical Institute, 2011)
Of the 2500 patients who had surgical intervention for benign biliary tract disease between 1977-1995, 385 (15.4%) had their common bile ducti (CBD) explored and of these 275 had stones present (11.0%). Choledochoduodenostomy was done in 220 cases. There were 165 women and 55 men making ratio of 3:1. Age ranged between 22-80 years (mean 50 years) with maximum incidence in 5th and 6th decade. Morbidity was 2.2 %. Mortality was nil in the series. "Sump" syndrome was not recorded in any cases however few nonospecific symptoms occured in some cases which responded well to conservative treatment. Choledochoduodenostomy should be performed as primary procedure in management of CBD stones as it is safe and effective.